Sosialisasi Motivasi Pendidikan Pada Siswa SMP Negeri 4 Sungai Raya Kepulauan Dalam Salah Satu Kegiatan Pengabdian Kepada Masyarakat Di Pulau Lemukutan - Julianto Julianto; Suci Athika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Education is something that can be used as a weapon in adapting to today's sophisticated era, improving education is something that should be fought for in improving the economy of a region in the future. Lemukutan Island has a lot of Natural Resources that can be processed, especially marine products and education is a facility that can accommodate the processing and management of Natural Resources on Lemukutan Island. Through Community Service this lecturer can provide educational motivation for the children of SMP Negeri 4 Sungai Raya Lemukutan Islands to continue their education in pursuing and achieving dreams. The focus on education is the main thing that children need to hold fast to develop a region, but to be able to always be in the corridor of education is not easy. Every generation has its own kind of challenges. In today's era, online games are a challenge that has mushroomed everywhere, games are not just a hobby, but more towards professions and needs. It will be very dangerous when there is a lack of parental supervision and students' lack of control over themselves in playing games. Reminding them of the dangers of playing online games is one way to keep directing them on the right educational path.